Surat Keputusan Pengangkatan Pegawai Sebagai Jaminan Kredit Di Bank - Tika Andarasni Parwitasari (STMIK Sinar Nusantara, 2011)
Economic conditions and development in Indonesia can not be separated from the role of the banking sector, role or function of banking here is as a